A agroecologia como ciência mediadora entre a formação do agrônomo e a agricultura sustentável - Gonçalves De Campos, Arnaldo; Jader Mello, Geison; Covari, Leone; Carbo, Leandro [UNESP]; Da Silva, Jorge Luiz; Feitoza Senra, Ronaldo Eustáquio; Barbosa Coelho, Maria De Fatima (My University, 2015)
Agro-ecology plays an important role in the implementation of sustainable development, and an agronomist can be a leading agent in the dissemination of that culture. In this perspective, a survey was carried out with the attendants of the course in Agronomy at the Instituto Federal de Educação, Ciência e Tecnologia do Mato Grosso, Campus Campo Novo do Parecis, Brazil. The object of the study was to analyze the participation of the academics in agro-ecological activities, seeking to observe the acceptance, perceptions and possible indications of incorporation of these principles in the training. The survey was conducted during the period July-December 2011. The approach was the qualitative method and the instruments used in data collection were participant observation and interviews during the activities. The results revealed the satisfaction of students in engaging in agro-ecological activities: Students developed concepts and incorporated the proposal of agro-ecology throughout the project. The contents of the agronomy course offered at the institution, in the perception of students, is strongly linked to the principles of conventional farming, not fully considering training to meet the challenges, and current and emerging demands of agriculture.
Agro-ecology as a mediating science between the training of the agronomist and sustainable agriculture